(untitled) (Journal of Oriental Studies, 2026)
Today, Turkish TV soap operas hold a significant place in the global film industry and have a profound influence on people’s increasing interest in Turkey and its culture. The article examines students’ perceptions of the use of Turkish TV series in the process of teaching Turkish as a foreign language in higher education institutions. The study is based on the hypothesis that Turkish TV soap operas stimulate students’ interest in Turkish and have a positive impact on language learning. The research aims to determine how Turkish soap operas motivate students to learn Turkish and their impact on teaching Turkish. Turkey’s increasing influence on the international stage, the popularity of Turkish TV series in recent years, and the growing interest among young people in the Turkish language and culture underscore the relevance of the research. The research was conducted among the students of Kazakhstan-American Free University, S. Amanzholov East Kazakhstan University, and Al-Farabi Kazakh National University. One hundred students participated in the study. The questionnaire developed in Google Forms revealed the impact of Turkish TV soap operas on students’ increased motivation in learning Turkish in higher education. In the study, descriptive method, quantitative method, and content analysis method were used. The results of enhancing their mastery of the Turkish language. The authors provide recommendations for integrating TV soap operas into the educational process. Keywords: foreign language teaching process, Turkish language teaching, Turkish culture, Turkish soap operas, integration of language and culture, motivation, language skills, cultural context.